Real and complex singularities - International Workshop on Real and Complex Singularities (Brazil 27 Jul - 8 Aug 2014); Nabarro, Ana Claudia; Nuno-ballesteros, Juan J.; Sinha, Raul Oset; Ruas, Maria Aparecida Soares (Providence : American Mathematical Society, 2016)
This volume is a collection of papers presented at the XIII International Workshop on Real and Complex Singularities, held from July 27-August 8, 2014, in Sao Carlos, Brazil, in honor of Maria del Carmen Romero Fuster's 60th birthday. The volume contains the notes from two mini-courses taught during the workshop: on intersection homology by J.-P. Brasselet, and on non-isolated hypersurface singularities and Le cycles by D. Massey. The remaining contributions are research articles which cover topics from the foundations of singularity theory (including classification theory and invariants) to topology of singular spaces (links of singularities and semi-algebraic sets), as well as applications to topology (cobordism and Lefschetz fibrations), dynamical systems (Morse-Bott functions) and differential geometry (affine geometry, Gauss-maps, caustics, frontals and non-Euclidean geometries). This book is published in cooperation with Real Sociedad Matematica Espanola.
Includes bibliographical references.
Keywords: Singularities (Mathematics) -- Congresses